Juvenile Idiopathic Arthritis in a Hospital Setting in Chad: A Study of 85 Cases - Garba, Harine Abdel Aziz; Bah, Adama; Bouchrane, Ramadhane; Hamid, Harine Abdel Aziz; Niasse, Moustapha; Saïdou, Diallo (European Scientific Journal, ESJ, 2025)
Introduction: Juvenile idiopathic arthritis (JIA) is the most common chronic inflammatory rheumatism in children. It remains poorly studied in sub-Saharan Africa. Objective: To describe the epidemiological, clinical, therapeutic and evolutionary features of JIA in a rheumatology department in Chad. Methods: This was a retrospective descriptive study involving 85 cases of JIA collected from January 2020 to September 2024. Demographic, clinical, biological, therapeutic, and follow-up data were analyzed. Results: Among 111 systemic disease cases, 85 were JIA. The mean age at disease onset was 11.2 years with a female-to-male ratio of 2.4. The most common forms were enthesitis-related arthritis (30.6%), RF-negative polyarthritis (30.6%), and oligoarthritis (18.8%). The average diagnostic delay was 4.2 years. The most frequent extra-articular manifestations were uveitis (15.3%) and lymphadenopathy (5.9%). Treatment included NSAIDs, corticosteroids, methotrexate, and etanercept in four cases. Three deaths were recorded. Outcomes were favorable in most cases, as assessed by CHAQ and JADAS scores. Conclusion: JIA is the most frequent pediatric systemic disease in our setting. Diagnosis remains delayed and access to innovative therapies is limited. Early diagnosis and structured follow-up should be strengthened.